Physical determinants of Division 1 Collegiate basketball, Women's National Basketball League, and Women's National Basketball Association athletes: With reference to lower-body sidedness - Spiteri, T.; Binetti, M.; Scanlan, A. T.; Dalbo, V. J.; Dolci, F.; Specos, C. (The Journal of Strength and Conditioning Research, 2019)
In female basketball, the assumed components of success include power, agility, and the proficiency at executing movements using each limb. However, the importance of these attributes in discriminating between playing levels in female basketball has yet to be determined. The purpose of this study was to compare lower-body power, change of direction (COD) speed, agility, and lower-body sidedness between basketball athletes participating in Division 1 Collegiate basketball (United States), Women's National Basketball League (WNBL) (Australia), and Women's National Basketball Association (WNBA) (United States). Fifteen female athletes from each league (N = 45) completed a double- and single-leg countermovement jump (CMJ), static jump, drop jump, 5-0-5 COD test, and an offensive and a defensive agility test. One-way analysis of variance with post hoc comparisons were conducted to compare differences in physical characteristics (height, body mass, age) and performance outcomes (jump, COD, agility assessments) between playing levels. Separate dependent t-tests were performed to compare lower-body sidedness (left vs. right lower limbs) during the single-leg CMJ jumps (vertical jump height) and 5-0-5 COD test for each limb within each playing level. WNBA athletes displayed significantly greater lower-body power (p = 0.01-0.03) compared with WNBL athletes, significantly faster COD speed (p = 0.02-0.03), and offensive and defensive agility performances (p = 0.02-0.03) compared with WNBL and Collegiate athletes. The WNBL athletes also produced a faster defensive agility performance compared with Collegiate athletes (p = 0.02). Furthermore, WNBA and WNBL athletes exhibited reduced lower-body sidedness compared with Collegiate athletes. These findings indicate the importance of lower-body power, agility, and reduced lower-body imbalances to execute more proficient on-court movements required to compete at higher playing levels.